Peripheral Neuropathy Outbreaks in Bhutan, 2020–2021 - Chhetri, Vishal; Dorji, Tshering; Monger, Adeep; Pokhrel, Hari Prasad (Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2023)
Thiamine (vitamin B1) deficiency can cause beriberi leading to cardiac involvement or, more commonly, peripheral neuropathy. Common causes of thiamine deficiency are alcohol use, maternal thiamine deficiency, poor dietary diversity, unhygienic food preparation, and unsafe cooking practices. This report presents an analysis of suspected peripheral neuropathy outbreaks recorded at the Royal Centre for Disease Control between 2020 and 2021. The suspected outbreaks were reported from schools and monastic institutes with the main complaints of numbness and swelling of lower limbs. Three of the four events were confirmed due to thiamine deficiency by laboratory analysis. Of 34 samples tested, 27 (79%) had thiamine deficiency, defined as a thiamine diphosphate (ThDP) level <75.0 nmol/L. The mean ThDP level was 56.5 nmol/L. There were no statistically significant differences in the average ThDP level among the patients of different age groups. Given the fact that micronutrient deficiency was established as the cause of the current peripheral neuropathy outbreaks, we recommend that the supply of fortified rice across both government and private institutes in the country be initiated. Holistic approaches should be implemented to reduce the burden of micronutrient deficiencies in the country.